Design of micro-hydro and seawater chemical energy for illuminating a floating anchored raft to improve the welfare of fishermen in Banyuwangi - Widjonarko Widjonarko; Triwahju Hardianto; Lintang Budiarti; Bukhori Muslim (Universitas Muhammadiyah Magelang, 2023)
Ten percent of fishermen in Muncar District, Banyuwangi, use floating rafts as their fishing equipment, equipped with generators as their source of electricity for lighting. However, the use of generators is considered less effective because they rely on scarce fuel oil, the price of which increases every year. To address these issues, this community service project aims to develop micro-hydro power plants and harness seawater chemical energy as an alternative to fuel-powered generators. The project commenced with observations and outreach to fishermen and village officials. Subsequently, the project progressed to designing a tool and applying it to one of the floating rafts as a feasibility test sample. The project concluded with the delivery of these tools to the fishermen after they were confirmed to be functioning properly. The electricity generated from a set of 20 voltaic cells reaches a maximum value of 9.15 V and still requires a DC-DC converter to power the 12 V LED lamp. This tool still necessitates additional power to ensure the electricity generated can meet the lamp's power requirements.